Financial Sector Reforms in Nepal - Shrestha, Ganesh Kumar (NRB Economic Review, 2004)
Financial sector is the backbone or engine of growth of any economy. It mobilizes and allocates financial resources most productively and efficiently and induces investment, increases employment opportunities and productivity, achieves growth targets and attains overall macro-economic development In a global financial system, each country has to reform its financial sector. The reform process should be properly sequenced. Nepal initiated financial sector reform in mid-1980s and HMG/N and Nepal Rastra Bank have been implementing comprehensive Financial Sector Reform Program since 2001. HMG/N has strongly committed for the reform of the financial sector in general and RBB, NBL, ADB/N and NIDC in particular. Much depends on the proper implementation of the Financial Sector Reform Program. The financial sector may invite financial crisis which may easily transfer to other sectors of the economy. As such, we have to be extra cautious for the financial liberalization and reforms of the financial sector.